El riesgo país en el Perú y sus factores determinantes, período 2010-2019 - Maslucán Rojas, Elisa Margarita (2021)
The main objective of this research is to identify the main determinants of the country in Peru during the period 2010 - 2019. In this way, based on the theoretical review on the issue and its antecedents, four groups of variables were identified: macroeconomic fundamentals, liquidity indicators, contagion variables and external shock variables. After a descriptive statistical analysis and the application of a multiple log-log regression model, it is concluded that the significant determinants of country risk in the period of analysis are the gross domestic product, exports, imports, the real exchange rate, the libor rate and the 30-year bond interest rate of the American markets, the differential of the bond yield of the Latin American markets, in addition to the lag of the EMBIG of the last two periods.